A patient-centered, coordinated care approach delivered by community and pediatric primary care providers to promote responsive parenting: pragmatic randomized clinical trial rationale and protocol - Jennifer S. Savage; Samantha M. R. Kling; Adam Cook; Lindsey Hess; Shawnee Lutcher; Michele Marini; Jacob Mowery; Shannon Hayward; Sandra Hassink; Jennifer Franceschelli Hosterman; Ian M. Paul; Chris Seiler; et al. (BMC, 2018)
Abstract Background Economically disadvantaged families receive care in both clinical and community settings, but this care is rarely coordinated and can result in conflicting educational messaging. WEE Baby Care is a pragmatic randomized clinical trial evaluating a patient-centered responsive parenting (RP) intervention that uses health information technology (HIT) strategies to coordinate care between pediatric primary care providers (PCPs) and the Special Supplemental Nutrition Program for Women, Infant and Children (WIC) community nutritionists to prevent rapid weight gain from birth to 6 months. It is hypothesized that data integration and coordination will improve consistency in RP messaging and parent self-efficacy, promoting shared decision making and infant self-regulation, to reduce infant rapid weight gain from birth to 6 months. Methods/design Two hundred and ninety mothers and their full-term newborns will be recruited and randomized to the "RP intervention" or "standard care control" groups. The RP intervention includes: 1) parenting and nutrition education developed using the American Academy of Pediatrics Healthy Active Living for Families curriculum in conjunction with portions of a previously tested RP curriculum delivered by trained pediatric PCPs and WIC nutritionists during regularly scheduled appointments; 2) parent-reported data using the Early Healthy Lifestyles (EHL) risk assessment tool; and 3) data integration into child's electronic health records with display and documentation features to inform counseling and coordinate care between pediatric PCPs and WIC nutritionists. The primary study outcome is rapid infant weight gain from birth to 6 months derived from sex-specific World Health Organization adjusted weight-for-age z-scores. Additional outcomes include care coordination, messaging consistency, parenting behaviors (e.g., food to soothe), self-efficacy, and infant sleep health. Infant temperament and parent depression will be explored as moderators of RP effects on infant outcomes. Discussion This pragmatic patient-centered RP intervention integrates and coordinates care across clinical and community sectors, potentially offering a fundamental change in the delivery of pediatric care for prevention and health promotion. Findings from this trial can inform large scale dissemination of obesity prevention programs. Trial registration Restrospective Clinical Trial Registration: NCT03482908. Registered March 29, 2018.